On Symmetric Riemann-Derivatives - S. Deb, (Indian Journal of Advanced Mathematics (IJAM), 2024)
The basic properties like monotoni city, Darboux property, mean value property of symmetric Riemann-derivatives of order n of a real valued function f at a point x of its domain (a closed interval) is studied. In some cases, function is considered to be continuous or semi-continuous.